APPLICATION OF IOT (INTERNET OF THINGS) TECHNOLOGIES FOR TECHNOLOGICAL MACHINES (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article analyzes the role and importance of IoT (Internet of Things) technologies in increasing the efficiency of technological machines in modern industrial enterprises. The possibilities of real-time monitoring, remote control, forecasting of technical maintenance and optimization of production processes through IoT technologies are scientifically highlighted. In addition to the practical advantages of these technologies, problems such as implementation costs, cybersecurity risks and shortage of qualified personnel are also considered in detail. The results of the study show that the implementation of IoT technologies based on a strategic approach serves to increase the competitiveness of industrial sectors.